A new genus for “Neocallichirus” grandis Karasawa & Goda, 1996, a ghost shrimp species (Decapoda: Axiidea: Callianassidae) heretofore known only by fossil materials - Komai, Tomoyuki; Yokooka, Hiroyuki; Henmi, Yumi; Itani, Gyo (Zootaxa, 2019)
A new genus of the family Callianassidae, Laticallichirus, is established for “Neocallichirus” grandis Karasawa & Goda, 1996, a ghost shrimp species heretofore represented only by fossil materials from the middle to upper Pleistocene of Japan. The newly collected specimens came from two Japanese localities: Numazu, Shizuoka Prefecture (Suruga Bay) and Tosa, Kochi Prefecture (Tosa Bay), included within the known geographical range derived from fossil records. The species identification was based on the close agreement in the cheliped morphology and the known fossil distributions. The new genus is assigned to the subfamily Callichirinae Manning & Felder, 1991, and compared with seven genera, Balsscallichirus Sakai, 2011, Callichirus Stimpson, 1866, Callichiropsis Sakai, 2010, Grynaminna Poore, 2000, Michaelcallianassa Sakai, 2002, Lepidophthalmus Holmes, 1904 and Podocallichirus Sakai, 1999, all characterized by the antennular peduncle being longer and stouter than the antennal peduncle. The new genus is characteristic in combination of the following characters: rostrum spiniform; maxilliped 3 devoid of exopod; ischium-merus of maxilliped 3 broadly operculiform; maxilliped 3 ischium devoid of crista dentata; major cheliped devoid of meral hook or associated lobe-like structure; tergites of the pleomeres 3–5 without conspicuous ornamentation; male pleopod 2 biramous, its endopod devoid of appendices interna and masculina; uropodal endopod suboval in shape; telson distinctly wider than long, with shallowly concave posterior margin. The genetic analysis using the mitochondrial 16S rRNA places the new genus as sister to Callichirus Stimpson, 1866, although bootstrap support for major branches is generally low. The newly collected specimens were found in burrows in soft sediments of shallow subtidal zone being accessible at low tide.